Methods and algorithms for molecular docking-based drug design and discovery - Dastmalchi, Siavoush, 1966-; Hamzeh-Mivehroud, Maryam, 1981-; Sokouti, Babak, 1978- (Advances in medical technologies and clinical practice (AMTCP) book series, 2016)
"This book investigates the evolution of pharmaceutical design and computational approaches in the field of molecular docking, highlighting theoretical backgrounds and emergent research in the area of computer-assisted drug design"--Provided by publisher.